Estudo teórico da Programação Linear e Modelagem Matemática como estratégia de ensino - Gonçalves, Bruno (2025)
n this study, we explore the use of Linear Programming Problems (LPPs), a topic traditionally covered only in Higher Education, as a teaching tool for students in High School. This approach is supported by the Base Nacional Comum Curricular, focusing on Mathematical Modeling as a teaching strategy. We present the main LPP theorems and their respective proofs. Additionally, we implemented the Simplex Method in the Python programming language to solve problems aimed at maximizing the objective function with inequality constraints of the type less or equal. Finally, we propose LPPs that can be applied in High School, along with their modeling, graphical solutions, and computational support. Our goal is to highlight the educational relevance and potential of LPPs in Mathematics teaching, as they can motivate students addressing aspects of Mathematics related to practical situations.